Past Success and Creativity over Time: A Study of Inventors in the Hard Disk Drive Industry - Audia, Pino G.; Goncalo, Jack A. (Management Science, 2007)
We integrate psychological theories of individual creativity with organizational theories of exploration versus exploitation to examine the relationship between past success and creativity over time. A key prediction derived from this theoretical integration is that successful people should be more likely to generate new ideas, but these ideas will tend to be less divergent as they favor the exploitation of familiar knowledge at the expense of the exploration of new domains. This prediction departs from the often-held view that people who generate more ideas will also generate ideas that are more divergent. Analyses of patenting in the hard disk drive industry support our prediction and indicate that collaboration with other inventors and organizational norms for exploration attenuate the tendency for successful individuals to generate increasingly incremental ideas.